Pengembangan Motorik Halus Anak Usia Dini melalui Kegiatan Kolase di RA Muslimat NU 032 Al Qoryah - Risa Alfiyah Ulfa Risa (CV Omah Kreator, 2026)
This study aims to analyze the development of early childhood fine motor skills through collage activities in Group A at RA Muslimat NU 032 Al Qoryah Bakalan. The study was motivated by children’s low fine motor abilities, particularly in hand-eye coordination during cutting, pasting, and arranging learning materials. This research employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings revealed that collage activities effectively improved children’s fine motor skills through tasks such as applying glue, arranging paper pieces, pasting according to patterns, and completing activities independently. The learning process included lesson preparation, provision of materials, teacher guidance, and evaluation activities. Supporting factors included collaboration between teachers and parents, as well as the use of attractive and varied learning media. Meanwhile, inhibiting factors included children’s unstable moods and limited learning resources. The novelty of this study lies in the implementation of play-based and exploratory collage activities combined with active teacher assistance to stimulate children’s fine motor coordination comprehensively. The study highlights that collage activities not only improve hand skills but also foster children’s independence, concentration, and active participation in the learning process. Therefore, collage activities can be used as an effective learning method to support fine motor development in early childhood education.